Lactulose synergizes with CpG-ODN to modulate epithelial and immune cells cross talk. Issue 1 (11th January 2019) - Mukherjee, R.; van de. Kaa, M.; Garssen, J.; Pieters, R. J.; Kraneveld, A. D.; Willemsen, L. E. M.
Abstract : Apart from being a prebiotic and laxative, lactulose has direct immunomodulatory effects. Abstract : Lactulose, a non-digestible oligosaccharide and functional food, promotes Bifidobacteria growth. Here we show that lactulose, beyond its prebiotic action, may have direct immunomodulatory effects as well. In synergy with CpG-ODN, a bacterial DNA mimetic, lactulose enhances basolateral concentrations of IFN-γ, IL-10, and galectin-9 in the co-culture model of epithelial and immune cells.